1996
DOI: 10.1021/om950800w
|View full text |Cite
|
Sign up to set email alerts
|

4-1,5-Cyclooctadiene)(η6-phosphinine)iron(0):  Novel Room-Temperature Catalyst for Pyridine Formation,1

Abstract: Two routes are described for the synthesis of (η4-1,5-cyclooctadiene)(η6-phosphinine)iron(0) complexes. A three-component reaction of iron vapor with COD and 2-(trimethylsilyl)-4,5-dimethylphosphinine at low temperature yields 20% (COD)(2-(trimethylsilyl)-4,5-dimethylphosphinine)Fe(0) (3), whereas ligand exchange of one COD ligand of the in situ prepared metal vapor product (COD)2Fe by 2-(trimethylsilyl)-4,5-dimethylphosphinine or (η1-2-chloro-4,5-dimethylphosphinine)Cr(CO)5 gives corresponding (COD)(phosphini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 30 publications
2
49
0
2
Order By: Relevance
“…Breit et al [4] have shown that substituted phosphinines coordinated in a h 1 fashion to rhodium can act as highly activated and selective catalysts for the hydroformylation of olefins. Likewise, complexes containing h 6 -phosphinines catalyse the synthesis of pyridines from alkynes and nitriles [5] and the cyclodimerisation of 1,3-butadiene. [6] In previous studies [7][8][9][10] we showed that the 2,4,6-tri-tertbutyl-1,3,5-triphosphabenzene, P 3 C 3 tBu 3 (1 a), readily undergoes [1 + 4] cycloaddition reactions with isoelectronic silylenes and (transition-metal-complexed) phosphinidenes (and in unpublished work [11] ) with isolobal In I and Ga I compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breit et al [4] have shown that substituted phosphinines coordinated in a h 1 fashion to rhodium can act as highly activated and selective catalysts for the hydroformylation of olefins. Likewise, complexes containing h 6 -phosphinines catalyse the synthesis of pyridines from alkynes and nitriles [5] and the cyclodimerisation of 1,3-butadiene. [6] In previous studies [7][8][9][10] we showed that the 2,4,6-tri-tertbutyl-1,3,5-triphosphabenzene, P 3 C 3 tBu 3 (1 a), readily undergoes [1 + 4] cycloaddition reactions with isoelectronic silylenes and (transition-metal-complexed) phosphinidenes (and in unpublished work [11] ) with isolobal In I and Ga I compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the greater reactivity of the sodium amide compared with the corresponding lithium reagent, the progress of the reaction was monitored by 5 ] and P 3 C 3 tBu 3 . [10,11] The reaction was complete after 3 days at room temperature, yielding, as expected, NaP 2 C 3 tBu 3 (singlet, d P = 187.4 ppm in THF) and the tricyclic compound 4 a.…”
mentioning
confidence: 99%
“…5,6 During the course of our investigations on functionalized phosphabenzenes, a novel methylthio substituted phosphinine has been prepared. Single crystals of this compound were obtained, which were subject to an X-ray crystal structure analysis.…”
Section: Introduction λmentioning
confidence: 99%
“…Zenneck and co-workers [80] developed an Fe(0) complex 42 catalyzed [2+2+2] cycloaddition of two molecules of alkynes and nitriles (Scheme 35), however, this approach gave low chemoselectivity (benezenes were the main products) and had a complicated procedure for catalyst preparation. A stoichiometric reaction between an Fe(+1) complex and alkynes was report by Guerchais and co-workers [81] with high chemoselectivity (Scheme 36).…”
Section: Scheme 34mentioning
confidence: 99%